UJI KONSENTRASI KINETIN DAN NAA TERHADAP MULTIPLIKASI EMBRIO AREN (Arenga pinnata (W) Merr) SECARA IN VITRO - Edri Wahyudi; Ernita Ernita; Fathurrahman Fathurrahman (UIR Press, 2013)
The objective of this reserach was to know the effect intereactionally and individually of Kinetin and NAA application on embryo multiplication for sugar palm. This research was conducted at the Biotechnology Laboratory Faculty of Agriculture Riau Islamic university Pekanbaru from October 2010 to January 2011. The experimental used the Completely Randomized Design with 2 factors. The first factor was K with 4 treatments; K0 (0 ppm), K1 (0.1 ppm), K2 (1.0 ppm), and K3 (10.0 ppm). The second factor was N with 4 treatments; N0 (0 ppm), N1 (0.1 ppm), N2 (0.5 pmm), and N3 (1,0 ppm). The observed parameters consisted of emergent shoot age (day), percentage of emergent shoot (%), shoot height (cm), and emergent root age (day). The obtained data were analyized using statistice technique and then test with 5% significant level. The result showed that interaction of Kinetin and NAA application had a significat effect on emergent root age with the best treatment of k1N0 30.66 days. Individually, kinetin affected significantly on emergent shoot age, percentage of emergent shoot, emergent root age with the best treatment of K2, and shoot height with the best treatment of K3. Furthermore, NAA hada a significant effect on emergent shoot age and shoot height with the best treatment of N3 and emergent root age with the best treatment of N0.